WAKAF BERBASIS AKAD MUAMALAH UNTUK MENINGKATKAN KETAHANAN PANGAN DI INDONESIA - Fauzia Ulirrahmi; Afthon Yazid (UIN Siber Syekh Nurjati Cirebon, 2022)
Food security can be achieved by the existence of adequate food land. The government has made efforts to implement land protection with the passage of Law No. 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land. The implementation of this law is constrained because it must be further implemented in derivative laws that are the domain of local governments. In addition, the large number of interests related to the use of land for use outside the agricultural sector is also a serious obstacle. This is further complicated by the passage of the Job Creation Law (Ombibus Law) which states that sustainable food agricultural land can be converted to realize public interests or national strategic projects (Article 122). This research is qualitative research with library sources using the analysis of contract theory in fiqh muamalah. The result is that waqf can serve as a safeguard for agricultural land which is now often converted, it can also serve as capital to support the agricultural sector with several contracts such as muzaro'ah, mukhabaroh, ba'i salam, and ijarah. These contracts will intensify productive agricultural activities with a broad distribution of profits. This activity can also be used with non-profit and commercial programs. The agreement is expected to improve food security in Indonesia and, in addition, the welfare of farmers who have been at a low economic level can be improved.Keywords: Food Security; Waqf; Contract; Mu'amalah